Preconceptions on Deddy Corbuzier’s Close the Door Podcast May 2025 Edition: The People of Papua Are Hungry - Rizky Anggraini; Rahayu Pujiastuti (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the types of preconceptions found in the May 2025 edition of Deddy Corbuzier's Close the Door podcast with the theme The People of Papua are Hungry. This study uses a qualitative approach with a descriptive method. The research data consists of narratives from sources that contain preconceptions. The data sources were obtained from seven Close the Door podcast videos aired in May 2025. Data collection techniques were carried out through documentation, downloading, non-participant observation, and recording. Data analysis techniques were carried out by describing. The data analysis procedure was carried out by transcribing, classifying, coding, interpreting, and concluding. The results of the study show that the presuppositions in Deddy Corbuzier's podcast edition of May 2025, themed ‘The Hungry People of Papua’, include existential, factual, lexical, structural, non-factual, and counterfactual presuppositions. Existential presuppositions arise when objects, figures, places, or groups are considered real. Factual presuppositions affirm facts or experiences that actually occurred. Lexical presuppositions indicate changes in circumstances, habits, or achievements. Structural presuppositions arise through the question words what, who, where, and when. Non-factual presuppositions mark imaginary or simulated activities. Counterfactual presuppositions present scenarios or desires that contradict reality, such as if, for example, hoping, wanting.